อุปกรณ์กระดาษตรวจวัดโลหะทรานซิชั่นด้วยเทคนิคการเปลี่ยนแปลงสี - อาทิตย์ แก้วอำไพ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
In this study, metal cation detection by using 3 dimension paper-based devices with colorimetric technique was investigated. This method utilized only a mobile phone device in light control box. Metal cations were analyzed by using image J program providing the R G B values of the picture. Paper based device consists of two parts. One is hydrophobic part which is coated by wax and another is clean paper. Direction of flow solution is based on diffusion, gravity force and capillary force. Among the Rhodamine B derivative 1 (Rho_B 1), Rhodamine B derivative 2 (Rho_B 2), Dimethylglyoxime (DMG), Carminic acid (CA) and Eriochrome black T (EBT) dyes, CA and EBT were selected as dyes for detection of metal cations in this experiment due to its ability to change the color in various metal cation. The color changes of CA and EBT dyes with various metal cations giving different R G B values can be applied to discriminate among metal cations by using principle component analysis (PCA). The results indicated that CA and EBT offer effective discrimination of Al³⁺, Zn²⁺, Ni²⁺, Fe³⁺, Mn²⁺ and Pb²⁺.